Resistência a inseticidas em populações de percevejo-do-colmo do arroz Tibraca limbativentris (hemiptera: pentatomidae) - Maciel, Diogo Nery (2016)
The increase in insecticide application for control the rice stalk stink bug Tibraca limbativentris Stal (Hemiptera: Pentatomidae) in irrigated rice in Brazil, has been reported by producers as responsible for loss of effectiveness of some insecticides commonly used to manage this insect and this is the base of this investigation. The insecticides used in this study were: bifenthrin, carbosulfan, etophenprox, λ-cyhalothrin, and thiametoxam. Six populations of insects were collected in producing areas of the states of Tocantins, Goiás and Santa Catarina, Brazil. Insect adults of each population were submitted to discriminant concentrations (LC95s) previously determined for the population collected in natural habitat in Santo Antônio de Goiás, and used as standard susceptible population. The frequency of individuals resistant in the population of Formoso do Araguaia was 76% for carbosulfan, 86% for bifenthrin, 72% for etofenprox, 80% for L-cyalothrin, and 80% for thyamethoxam. Although the frequencies of resistant individuals can be considered low to moderate, it is first report of resistance of T. limbativentris to insecticides. These results indicate the resistance development to other insecticides with different mode of actions, with emphasis to the stink bug populations of Formoso do Araguaia-TO. These results also indicates a possible occurrence of crossed a resistance or multiple in that population.